2015
DOI: 10.1111/1750-3841.12976
|View full text |Cite
|
Sign up to set email alerts
|

Taste Detection Thresholds of Resveratrol

Abstract: Resveratrol is a polyphenol that is associated with numerous health benefits related to heart disease, cancer, diabetes, and neurological function. The addition of this compound to food products would help to deliver these health benefits to the consumer. However, bitterness associated with resveratrol may impart negative sensory qualities on the food products into which resveratrol is added; thus, decreasing consumer acceptability. This concern may be resolved by encapsulating resveratrol through spray drying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
(43 reference statements)
0
12
1
Order By: Relevance
“…Several studies in lemurs, mice, honey bees, and humans suggest that resveratrol may affect food intake due to its bitter taste [ 65 , 80 , 81 , 82 , 83 ], which may in turn affect stress response and metabolism. However, in the current fly study, we did not observe significant differences in feed intake between groups ( Figure 1 ).…”
Section: Discussioncontrasting
(Expert classified)
“…Several studies in lemurs, mice, honey bees, and humans suggest that resveratrol may affect food intake due to its bitter taste [ 65 , 80 , 81 , 82 , 83 ], which may in turn affect stress response and metabolism. However, in the current fly study, we did not observe significant differences in feed intake between groups ( Figure 1 ).…”
Section: Discussioncontrasting
(Expert classified)
“…Gaudette and Pickering ( 2011 ) reported an increase in the perception of bitterness with increasing concentrations of resveratrol added to wine. To minimize the effect of resveratrol on the organoleptic properties of the food, techniques such as encapsulation of resveratrol by spray-drying was suggested by Koga et al ( 2015 ) to reduce the perception of bitterness. They reported a higher taste detection threshold for resveratrol (313 μg/mL) encapsulated with sodium caseinate than unencapsulated resveratrol (90 μg/mL) in protein solution (Koga et al, 2015 ).…”
Section: Application and Efficacy Of Resveratrol In The Food Systemmentioning
confidence: 99%
“…To minimize the effect of resveratrol on the organoleptic properties of the food, techniques such as encapsulation of resveratrol by spray-drying was suggested by Koga et al ( 2015 ) to reduce the perception of bitterness. They reported a higher taste detection threshold for resveratrol (313 μg/mL) encapsulated with sodium caseinate than unencapsulated resveratrol (90 μg/mL) in protein solution (Koga et al, 2015 ). To date, studies on the sensory evaluation of resveratrol in the food system are still limited, thus further work is needed to improve the utilization of resveratrol as a food preservatives by minimizing its taste altering effect.…”
Section: Application and Efficacy Of Resveratrol In The Food Systemmentioning
confidence: 99%
“…The results of our prior research demonstrated that resveratrol encapsulated within a sodium caseinate matrix had a significantly higher stability and higher taste detection threshold in comparison to unencapsulated resveratrol (Koga and others ). This indicated that the encapsulation within a sodium caseinate matrix provided stability and masked negative sensory attributes of resveratrol.…”
Section: Introductionmentioning
confidence: 73%